ACCEPTABILITY OF BREADFRUIT ( ARTOCARPUS ALTILIS) FLOUR CAKES AND COOKIES: BASIS FOR TECHNO-GUIDE - Añora, JG; Quiño, CD; Medalle, AY; Jopia, MLT (Journal of Agriculture and Technology Management; Tropical Technology Journal Volume 11 No. 3-4, 2008, 2008)
This experimental research was conducted to determine the acceptability of breadfruit cake and cookies in different concentrations: 25%, 50%, 75% and 100% of flour based on sensory evaluation using descriptive and preference testing and to prepare a techno guide for students based on the findings. The 60 respondents were divided into two groups. The control variables of the study are the different commercial flour, namely: 1st class cake flour, 2nd class cake flour, wheat flour and camote flour and the experimental variable is the breadfruit flour, all within 100% concentration of each kind. The result of the laboratory analysis of the samples of breadfruit flour as certified of by the Department of Science and Technology Regional; Office no.7 Regional Standards and Testing revealed the nutritional component in percent such as: ASH – 3.56%, Moisture – 12.2%, Total Fat – not detected ​